The Impact of the Iraqi Government's Financial Policy on Reduction of Unemployment Rates During the COVID-19 Pandemic - Hasan, Basima (Technium Social Sciences Journal, 2024)
This research paper aimed at analyzing the role of the financial policy taken up by the Iraqi government in confronting the outbreak of the COVID-19 pandemic and mitigating the repercussions of the pandemic on unemployment. It relied on quantitative and qualitative methods to analyze and evaluate the effects of financial policy on unemployment rates. Several international indicators were used, such as the Oxford University Government Response Tracker (OXCGRT) to know the strength of the stimulus package adopted by Iraq. The Principal Component Analysis (P) methodology was also used to analyze the composition of the stimulus financial policy taken. The results of the analysis generally came up with the fact that the the role of financial policy adopted by Iraq in promoting economic growth and accelerating recovery from the repercussions of the pandemic was significant on unemployment rates, depending on the size of that fiscal policy in Iraq.